2019
DOI: 10.1249/mss.0000000000001890
|View full text |Cite
|
Sign up to set email alerts
|

Activity Tracker to Prescribe Various Exercise Intensities in Breast Cancer Survivors

Abstract: Purpose: To prescribe different physical activity (PA) intensities using activity trackers to increase PA, reduce sedentary time, and improve health outcomes among breast cancer survivors. The maintenance effect of the interventions on study outcomes was also assessed. Methods: The Breast Cancer and Physical Activity Level pilot trial randomized 45 breast cancer survivors to a home-based, 12-wk lower (300 min•wk−1 at 40%-59% of HR reserve) or higherintensity PA (150 min•wk−1 at 60%-80% of HR reserve), or no PA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
93
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 47 publications
(96 citation statements)
references
References 55 publications
1
93
2
Order By: Relevance
“…No statistically significant effects on HRQoL (using the FACT scales) were observed at either 12‐ or 24‐week follow‐up. Finally, McNeil and colleagues randomized 45 breast cancer survivors to a home‐based exercise program that included a Polar A360(R) activity tracker combined with goal‐setting and follow‐up phone calls . Similar to our results, participants reported increases in MVPA and reduced sedentary time, but no changes in both generic (SF‐12) or disease‐specific (using the FACT scales) HRQoL.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…No statistically significant effects on HRQoL (using the FACT scales) were observed at either 12‐ or 24‐week follow‐up. Finally, McNeil and colleagues randomized 45 breast cancer survivors to a home‐based exercise program that included a Polar A360(R) activity tracker combined with goal‐setting and follow‐up phone calls . Similar to our results, participants reported increases in MVPA and reduced sedentary time, but no changes in both generic (SF‐12) or disease‐specific (using the FACT scales) HRQoL.…”
Section: Discussionsupporting
confidence: 80%
“…Few randomized controlled trials examining distance‐based approaches to promoting physical activity in cancer survivors have used wearable activity trackers . Only a few studies testing wearables have reported patient reported outcomes such as HRQoL and fatigue . For example, in one randomized trial of African American breast cancer survivors (N = 35), survivors were randomized to either a FitBit device combined with access to a web‐based health platform (SparkPeople) group, or a waitlist control group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Current research suggests that fitness watches can increase PA and could, theoretically, be used in combination with other medical recommendations to improve health parameters in those with chronic disease. For example, activity monitors (or fitness watches), in combination with other lifestyle interventions, appear to be successful at increasing PA in obese men and women [11], depressed and alcohol-dependent women [12], and breast cancer survivors [13]. In one study, authors examined the ability of a fitness watch to increase moderate to vigorous PA in overweight/obese adults over six weeks, while also examining if the addition of encouraging/reminder text messages (SMS) to a participant’s cell phone would further influence PA.…”
Section: Can a Fitness Watch Help Someone With A Chronic Disease Imentioning
confidence: 99%
“…Kajiwara et al [1] highlight the importance of assessing participant acceptance of wearable technology. In the Breast Cancer and Physical Activity Level (BC-PAL) pilot trial, acceptance or wear time of the activity tracker was not directly assessed [2]. However, the participants' perspectives of wearable technology were expressed in the semi-structured interviews, as presented by Kokts-Porietis et al [3].…”
mentioning
confidence: 99%